1997
DOI: 10.1136/gut.40.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bone density in patients with inflammatory bowel disease.

Abstract: Results-There was a high prevalence of low bone mineral density (prevalence of T scores <-1.0 from 510/o-77%; T scores <-2-5 (osteoporosis) from 170/o-28%) with hips being more often affected than vertebrae (p<0-001). Reduced bone mineral density did not relate to concurrent or past corticosteroid intake, or type, site, or severity of disease. Whereas calcium homeostasis was normal, bone markers showed increased bone resorption without a compensatory increase in bone formation. Conclusions-The greater prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
219
11
15

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(257 citation statements)
references
References 23 publications
12
219
11
15
Order By: Relevance
“…1,2 Low BMD in IBD can be seen both in males and females, and may occur in relatively young patients. 3 Osteoporosis is an important cause of morbidity because of the increased risk of fragility fractures; the fracture risk reported in Crohn's disease (CD) is 6%.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Low BMD in IBD can be seen both in males and females, and may occur in relatively young patients. 3 Osteoporosis is an important cause of morbidity because of the increased risk of fragility fractures; the fracture risk reported in Crohn's disease (CD) is 6%.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of osteopenia in IBD range from 31 to 59% and osteoporosis from 5 to 41%. Various studies exploring the cause of low BMD in IBD found a significant correlation between glucocorticoid treatment and decreased BMD (3,5,17,28,29). Glucocorticoids, such as prednisolone, are wellknown drugs for their potent anti-inflammatory and immunosuppressive properties.…”
mentioning
confidence: 99%
“…Studies of bone marker levels in patients with IBD have produced conflicting results. While some studies of have reported increased levels of bone resorptive markers without a compensatory increase in formation markers (31)(32)(33)(34)(35) , other studies have reported reduced levels of markers of bone formation and no difference in resorptive markers (36) , elevated levels of both types of markers (37)(38)(39)(40) or indeed no difference in markers (41) between patients with IBD and control subjects. However, in addition to differences in the biochemical markers used, some caution is also warranted in comparing the results of some of these studies because of major differences in the various populations of patients with IBD that were studied, especially in relation to the type of disease (CD v. UC), corticosteroid usage and disease activity (active disease v. disease remission) (42) .…”
Section: Risk Factors For Osteoporosismentioning
confidence: 99%